The Effect of Consumer Confidence and Customer Experience on Consumer Satisfaction in Anteraja Cirebon SS Kedawung Expedition Services - Soesanty Maulany (Journal of Bussines Management Basic, 2023)
his study aims to test the influence of Consumer Confidence and Customer Experience variables on Consumer Satisfaction in Anteraja Cirebon SS Kedawung expedition services. The research method used is a quantitative method with an associative type of research. Sampling technique using the Incidental Sampling technique with a sample of 96 respondents. Data collection method using questionnaires to respondents who have used Anteraja expedition services at least 1 transaction. Data analysis methods using validity tests, reliability, classical assumptions, multiple regression analysis as well as t-tests and ftests processed through IBM SPSS 26 applications